Assembleia de espécies na restauração por semeadura direta em área de Floresta Estacional - Dutra, Felipe Bueno (2021)
Nowadays, the technique of direct sowing has been recognized as the most viable and economical alternative in large-scale restoration. Thus, the objectives of the work were to analyze how direct sowing methods provided diversity and density of species and how this affected the assembly of plants in order to indicate potential or suitable species for direct sowing. The study areas are located in Anhembi-SP inserted in zones of Seasonal Forest, where eight treatments were tested evaluating the soil preparation (harrowing or subsoiling), the seeds distribution (manual or mechanized) and the density of sowing (125,000 to 250,000 seeds.ha-1 with 64 species, in different combinations during the critical emergency period from 30 - 150 days after sowing. The harrowed area with manual sowing and 250,000 seeds. ha-1 (1B) was the one with the highest plant density (13,400 ind.ha-1) but the area with subsoiling, manual seeding and sown with 125,000 seeds.ha-1 (5C / 50%) obtained the higher richness (S = 17) and diversity (H '= 2.42) of species, but with a low density (5.200 ind.ha-1). . The higher richness was from the Fabaceae family (11 species), followed by the Malvaceae (4 species), Anacardiaceae and Bignoniaceae (3 species). The species Mimosa bimucronata (DC.) Kuntze (0,092 ind.m²) Mabea fistulifera Mart. (0,074 ind.m²), Bixa orellana L. (0,065 ind.m²) and Anacardium occidentale L. (0,043 ind.m²) showed the highest densities between treatments. The study of the species assemblage in its initial trajectory allowed to evaluate the factors that influence the potential of species establishment and showed the importance of species composition, soil preparation and seed distribution in emergence and initial density in direct sowing.